ON THE SOLUTIONS OF SOME PROBLEMS OF THE THEORY OF FILTRATION - A. G. Balamirzoev; A. M. Zerbaliev; D. N. Selimkhanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In terms of the application of the law Darcy considered the problem of constructing complex potentials filtration flows with discontinuities in the form of concentric circles, and filtration areas with boundaries in the form of a square and isosceles rectangular triangle. The method of images singular points (the method of reflections).